Sujeitos diaspóricos e negociações identitárias: o entre-lugar em Brazil-Maru e Sonhos Bloqueados - Otenio, Marta Matsue Yamamoto [UNESP] (2015)
In this contemporary world it is strongly discussed the issue of plural identities, hyphenated individuals, mestizos, which stimulates the individuals to the ceaseless search for identity construction. The transition from a feudal era into modernization forced thousands of Japanese to search for better conditions of life in overseas lands. In the context of Japanese Diaspora to Brazil, we intend to analyze the traces of cultural hybridity in the way of life of these immigrants represented in literature. At first, we can note a certain resistance to assimilation of the Brazilian culture, as well as an aversion to the other culture. However, on the assumption that a cultural hybridization process is inevitable to identities construction in diasporic conditions, these immigrants had to negotiate the inclusion of Brazilian customs in their cultural traditions. In this sense, the present work has the main purpose to point the main cultural hybridizations acquired by these immigrants and Japanese descendants. Thereby, the in-between seems to be a welcome space that enables the review of principles of crystallized structure units and then, to allow a plasticity in the identity negotiation of this diasporic individual. Therefore, the research has as main focus the novels Sonhos bloqueados, by Japanese-Brazilian Laura Honda-Hasegawa and Brazil-Maru, by Japanese- American Karen Tei Yamashita. Honda-Hasegawa and Yamashita are two Japanese descendant writers that give voice to their female characters and stimulate us to discuss how the identities are complex in post-modernity, breaking with the idea of centralized and fixed identity. Moreover, even if Karen Tei Yamashita and Laura Honda-Hasegawa are innovators, both still remain conservatives